2008
DOI: 10.1103/physrevlett.101.266803
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Kondo Effect inCoCunClusters Atom by Atom

Abstract: Clusters containing a single magnetic impurity were investigated by scanning tunneling microscopy, spectroscopy, and ab initio electronic structure calculations. The Kondo temperature of a Co atom embedded in Cu clusters on Cu(111) exhibits a non-monotonic variation with the cluster size. Calculations model the experimental observations and demonstrate the importance of the local and anisotropic electronic structure for correlation effects in small clusters.PACS numbers: 68.37. Ef,72.15.Qm,73.20.Fz Nanomete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
64
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 33 publications
3
64
1
Order By: Relevance
“…Recently, however, nanocontacts made from Fe, Co, or Ni have been reported to display Kondo effect 10,11 . This has been infered from the observation of Fanolineshapes 12 in the low-voltage conductance characteristics similar to those observed in recent STM experiments with magnetic adatoms on metal surfaces [13][14][15][16] . The observation of the Kondo effect in Fe, Co, and Ni nanocontacts is rather surprising since these materials are strong ferromagnets as bulk materials.…”
Section: Introductionsupporting
confidence: 80%
“…Recently, however, nanocontacts made from Fe, Co, or Ni have been reported to display Kondo effect 10,11 . This has been infered from the observation of Fanolineshapes 12 in the low-voltage conductance characteristics similar to those observed in recent STM experiments with magnetic adatoms on metal surfaces [13][14][15][16] . The observation of the Kondo effect in Fe, Co, and Ni nanocontacts is rather surprising since these materials are strong ferromagnets as bulk materials.…”
Section: Introductionsupporting
confidence: 80%
“…These results fit in well with previous studies, which have shown the possibility of tailoring the electronic structure of metal atoms and complexes by ligand attachment [31][32][33][34] and atom-by-atom manipulation. 35 In addition, we find evidence for adorption of NH 3 in other sites of the FePc monolayer/Au(111) system. We have used temperature-programmed XPS (TP-XPS) to characterize these adsorbate states and find that NH 3 in these sites is more weakly bonded than when adsorbed on the FePc iron center.…”
Section: Introductionmentioning
confidence: 65%
“…To this end, we first consider the single impurity Anderson model with graphene providing the host electronic structure and compare to a simple model of a usual metal surface. With this background, we turn to a more realistic ab initio based description of magnetic impurities on graphene and discuss the case of Co adatoms as in the recent experiment by Manoharan et al 19 By comparison to Co on Cu ͑111͒, an extensively studied system, [5][6][7] possessing also hexagonal symmetry of the surface, we will demonstrate the importance of impurityinduced resonances in graphene 20 and the particular sensitivity of the q factor to orbital symmetries. Furthermore, we analyze model s-wave impurities being bound to different sites of the graphene lattice and show that a strong adsorption site dependence of Fano factors in STM experiments can be expected there.…”
Section: Introductionmentioning
confidence: 97%
“…However, large interest in this phenomenon has been revived recently since STM has been revealing the intricacies of Kondo effect at metal surfaces, caused by d and f adatoms. [2][3][4] The rich electronic structure of threedimensional metals like Cu, in general, controls impurity effects at surfaces [5][6][7] and the effects turned out to depend strongly on atomistic details. This requires a realistic description of the magnetic impurity, e.g., taking into account the detailed bonding geometry, to understand the electronic spectra of these structures.…”
Section: Introductionmentioning
confidence: 99%